Laser shock dynamic compaction of aluminum–copper (Al–Cu) composite metal powder - Maomao Cui; Zhen Dong; Tao Wang; Xiao Wang; Wenxiang Sun; Wenkai Shen; Huixia Liu (Journal of Materials Research and Technology, 2023)
Laser impact dynamic compaction experiments and 2D multi-particle finite element method (MPFEM) simulations were carried out on aluminum–copper (Al–Cu) binary-based composite powders. Al–Cu compacts with densities of about 95% were successfully prepared at the maximum laser energy of 1.8 J. Research trends indicate that higher power lasers could nearly achieve the theoretical densities. Analysis of the influence laws of laser energy and copper powder mass fraction on the densities of Al–Cu compacts was carried out, and the effects of microstructure and microhardness of Al–Cu compacts on their mechanical properties were investigated, as well as the stresses and velocities in the dynamic compaction process of Al–Cu composite powders were analyzed. The results showed that the relative densities of composite powder compacts of Al-5 wt%Cu gradually exceeded those of Al-10 wt%Cu and Al-15 wt%Cu with the increase of laser energy. In laser impact dynamic compaction the mechanism of inter-particle joining was solid-state press-welding, and the increase in the hardness of the Al–Cu compacts could be attributed to the inherent hardness of the hard particles. The upper particles have a localized maximum velocity of more than 300 m/s, which met the explosion welding velocity, thus localized cold welding occurred and contributed to the inter-particle connection.